Analysis of Fusion Cross Sections in the Be-9 Projectile Breakup on Different Target Nuclei - Mukeru, B.; Tomio, Lauro [UNESP] (Springer, 2020)
We present a theoretical study of total fusion (TF), complete fusion (CF), and incomplete fusion (ICF) cross sections in the breakup of Be-9 (described as n -Be-8) projectile on Sn-124, Sm-144 and Pb-208 target nuclei. We use the continuum discretized coupled-channel formalism together with a sum-rule model, by extending an approach outlined in Mukeru et al. (Nucl. Phys. A 996:121700, 2020) to another weakly bound projectile in different targets. The applicability of the model to incident energies below and around the Coulomb barrier is verified, being confirmed for all three reactions an empirical energy-dependent cutoff angular momentum expression. We show that the TF and ICF cross sections are strongly dependent on the projectile binding energy epsilon(b), whereas the CF is weakly affected by that. Despite this weak dependence, the CF contribution to the TF cross section becomes more suppressed by decreasing epsilon(b). The dependence of the ICF probability on the breakup threshold is also highlighted.
Keywords: Fusion reactions; Cross sections; Be-9 breakup